2001
DOI: 10.1080/089419201750111056
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Public Participation: Fairness in Natural Resource Decision Making

Abstract: Perceptions of justice in decision outcomes and processes increases trust, support for authorities, and satisfaction with unfavorable outcomes (Lind and Tyler 1988). However, very little research has been done to apply justice concepts to natural resource decision making contexts (an exception is Lauber and Knuth 1997;1998). In the study presented here, two rounds of focus groups with public participants in the Northern Lower Michigan Ecosystem Management Project were conducted. Participants were asked to desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
153
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(164 citation statements)
references
References 11 publications
6
153
1
4
Order By: Relevance
“…The theory of procedural fairness posits that the perception of equity or fairness in the decision-making process increases the acceptability of decision outcomes, even in cases where values or interests conflict (Lind and Tyler 1988). Research in this area has identified strategies for promoting relationship building (Frenz et al 2000;McCool et al Guthrie 2001) and ensuring fairness (Tyler and Degoey 1995;Lawrence and others 1997;Hunt and Haider 2001;Smith and McDonough 2001;McCool and Gothrie 2001) in public involvement processes. For instance, Smith and McDonough (2001) conducted focus groups with participants in a collaborative decision-making process.…”
Section: The Concept Of Trust In Natural Resources Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The theory of procedural fairness posits that the perception of equity or fairness in the decision-making process increases the acceptability of decision outcomes, even in cases where values or interests conflict (Lind and Tyler 1988). Research in this area has identified strategies for promoting relationship building (Frenz et al 2000;McCool et al Guthrie 2001) and ensuring fairness (Tyler and Degoey 1995;Lawrence and others 1997;Hunt and Haider 2001;Smith and McDonough 2001;McCool and Gothrie 2001) in public involvement processes. For instance, Smith and McDonough (2001) conducted focus groups with participants in a collaborative decision-making process.…”
Section: The Concept Of Trust In Natural Resources Managementmentioning
confidence: 99%
“…Research in this area has identified strategies for promoting relationship building (Frenz et al 2000;McCool et al Guthrie 2001) and ensuring fairness (Tyler and Degoey 1995;Lawrence and others 1997;Hunt and Haider 2001;Smith and McDonough 2001;McCool and Gothrie 2001) in public involvement processes. For instance, Smith and McDonough (2001) conducted focus groups with participants in a collaborative decision-making process. Their analysis revealed five themes essential to perceptions of fairness, including representation, voice, consideration, logic, and desired outcomes.…”
Section: The Concept Of Trust In Natural Resources Managementmentioning
confidence: 99%
“…This approach to justice and trust describes well the identified public participation challenges and local perspectives on energy development projects (King et al 1998, Gross, 2007Cain & Nelson 2013). 'Distributive justice' concerns fairness in the outcome, that is the distribution of costs and benefits (for more details about distributive justice see for instance Skitka et al 2003, Gross 2007, whereas 'procedural justice' refers to general principles of citizen control, democracy and fairness in the process within which decisions are reached (Smith and McDonough 2001). In a just process, participants should be informed while participation should be broad, and decision-making power shared (Laird 1993;Leventhal et al 1980, cited in Smith andMcDonough 2001).…”
Section: Theoretical Perspectives On Public Participation and Justicementioning
confidence: 99%
“…However, an alternative perspective contests the value of deductive theory-based evaluations, arguing that universal goals and criteria are less important than the specific goals of those involved in participatory efforts (Chess and Purcell, 1999), which may vary in different situations. In this perspective, participants themselves describe what effectiveness or success means to them within a given context (McCool and Guthrie, 2001;Smith and McDonough, 2001). Blackstock et al (2007) argue, along similar lines, that the evaluation of participatory processes should itself be participatory with stakeholders selecting and applying the evaluation criteria.…”
Section: Introductionmentioning
confidence: 99%